Modeling of dual‐factor drag correction model for bubbly flow under elevated pressure - Gao, Yibo; Geng, Linlin; Verdin, Patrick G.; Fall, Ibra; Zhang, Ruijie; Tian, Zhongjie; Zhang, Desheng (Wiley, 2024)
A pressure correction method is proposed considering the influence of a dual factor. The applicability of a pressure correction method coupled with a drag model is discussed along with the accuracy of the simulation results obtained by such a pressure correction method. It is found that the present pressure correction method combined with the DBS (dual bubble size) drag model can accurately reflect the changing trend of gas holdup distribution with pressure. It is also established that results from this model applied to a bubble column match well with the experimental data. Finally, when compared with other pressure correction models, the proposed model shows better robustness in three‐dimensional simulations and can predict radial gas holdup distributions with better accuracy.
Special Issue: 8th International Conference on Fuel Cell & Hydrogen Technology – 3rd Symposium on Fuel Cell and Hydrogen Technology 2023 (ICFCHT-SFCHT 2023)
Keywords: 40 Engineering; 4019 Resources Engineering and Extractive Metallurgy; Bioengineering; Chemical Engineering; 4017 Mechanical engineering; Bubble column; Computational fluid dynamics; Drag; Elevated pressure; Gas holdup